2017
DOI: 10.1097/md.0000000000005964
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis for salivary gland adenoid cystic carcinoma in southern china

Abstract: Adenoid cystic carcinoma (ACC) is characterized by slow growth, frequent local recurrences, and high incidence of distant metastasis (DM). The aim of this study was to evaluate predictive factors for local-regional (LR) recurrence, DM, and survival in ACC.A retrospective review of the medical records for patients with salivary glands ACC from 1990 to 2015 was performed. The clinical parameters were assessed to identify correlations with the development of LR recurrence, DM, and survival of these patients.Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 23 publications
4
60
2
3
Order By: Relevance
“…Adenoid cystic carcinomas (ACC) represent approximately 10% of salivary gland tumors and less than 1% of all head and neck tumors . Given its rarity, the optimal management of nonmetastatic ACC has been influenced by retrospective reviews from large centers rather than randomized trials . ACC grow relatively slowly compared to other head and neck cancers, have lower risk of lymph node metastases, and have high propensity for perineural invasion .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adenoid cystic carcinomas (ACC) represent approximately 10% of salivary gland tumors and less than 1% of all head and neck tumors . Given its rarity, the optimal management of nonmetastatic ACC has been influenced by retrospective reviews from large centers rather than randomized trials . ACC grow relatively slowly compared to other head and neck cancers, have lower risk of lymph node metastases, and have high propensity for perineural invasion .…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy has been investigated, but low response rates have been disappointing . The standard therapy for localized disease is surgical resection followed by adjuvant radiotherapy …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, many clinical AdCC studies have reported that poor prognosis is associated with pathological features such as AdCC type and grade (4). Histological specimens can be divided into three groups: tubular, cribriform, or solid.…”
mentioning
confidence: 99%